Pengembangan Media Pembelajaran E-Comic Interaktif untuk Meningkatkan Literasi Membaca Peserta Didik di MI Mahir Ar-Riyadl Surabaya - Sasmitha, Eka; El-Yunusi, Muhammad Yusron Maulana (WASIS : Jurnal Ilmiah Pendidikan, 2024)
Based on the background experienced by children aged 6 years regarding the lack of reading ability due to the inappropriate influence of digitalization, The researcher aims to improve reading literacy skills with interactive learning media in the form of e-comics. This research method uses Research and Development (RD) with a 4D model modified to 3D. Data collection was carried out based on the results of interviews, validation by teachers and lecturers as well as pretest and posttest carried out by students. The media validation results with an average score of 95% can be categorized as very valid, then for the practicality of e-comic it got a score above 81% which is categorized as very responsive. This interactive e-comic is also categorized as effective to use by analyzing using the t test with a significant value of 5%. Therefore, interactive e-comics can be used as a further learning medium to increase students' reading interest